Pengaruh Sistem Upah dan Jaminan Sosial terhadap Kesejahteraan Pakerja Perkebunan Kelapa Sawit KJP Cipta Prima Sejahtera di Desa Saka Tamiang - Fahruddin; Rizki Fadiah (Bulletin of Community Engagement, 2024)
This research is based on how the wage system, social security and welfare level of KJP Cipta Prima Sejahtera oil palm plantation workers, where it is currently seen that many workers' rights are not fulfilled. Such as wages below the UMK and social security for workers is not fulfilled. This study aims to determine and analyze the influence of the wage system and social security on the welfare of KJP Cipta Prima Sejahtera oil palm plantation workers in Saka Tamiang Village. The type of this research is field research with a quantitative descriptive method. Data collection techniques are by questionnaires and documentation. The subjects of this study were KJP Cipta Prima Sejahtera oil palm plantation workers, the sample determination used a saturated sample technique totaling 32 respondents. Data analysis techniques with the IBM SPSS Version 22 program. The results of the study prove that partially the wage system has a positive effect on worker welfare (0.011 <0.05) and social security has a positive effect on worker welfare (0.021 <0.05). The wage and social security system simultaneously has a positive effect on the welfare of oil palm plantation workers at KJP Cipta Prima Sejahtera in Saka Tamiang Village (0.003 < 0.05).